Sosialisasi Pishing Guna Mengedukasi Ibu-Ibu Pkk Dukuh Brajan Dalam Antisipasi Kejahatan Siber - Fauzan Imam; Iqbal Aditya Ferryanto; Hardika Khusnuliawati (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
In this era of technological development and widespread use of social media, Indonesian people are increasingly connected over long distances. However, despite its benefits, the use of social media also opens up opportunities for criminal acts, especially in the form of phishing. Phishing is a criminal act that targets sensitive information via email, SMS, and websites. Through community service activities in Sindon Village, especially Dukuh Brajan, the dangers of phishing were disseminated to PKK.. The research results showed that socialization was able to increase PKK understanding of the characteristics of phishing, such as the use of certain agency names, urgent sentences, fake links, dangerous files and personal numbers. Phishing outreach can be an effective effort to prevent phishing attacks in society. Thus, it is hoped that this activity can make a positive contribution in protecting the public from phishing threats in cyberspace.